European destination regions and social exclusion challenges. (4th January 2023) - Russo, Antonio Paolo; Valente, Riccardo
This paper presents a typology of European regions according to the type, mix and magnitude of human mobilities attracted over the 2008-2018 period, tourists being one of them, but extending to the related movement of different cohorts of migrants. Regional clusters are then assessed in terms of their social performance in domains such as health, material conditions, housing, and labour. Significant associations between regional types and social trends are interpreted in the light of potential factors affecting these outcomes. Results point to the uneven repercussions of housing unaffordability in the fastest growing destination regions, on the polarisation of living conditions in the European 'star destinations' and on the challenge of precarious labour, especially for migrant workers, in established mature destinations. In a stage of reignition of tourism activity after the COVID-19 crisis, these insights are meant to contribute to the recovery debate, informing about key social issues and vulnerabilities which, in specific regional contexts, could have been amplified by the current crisis.